On reducing anisotropy in 3D printed polymers via ionizing radiation - Shaffer, Steven; Yang, Kejia; Vargas, Juan; Di Prima, Matthew A.; Voit, Walter (Polymer (Guilford), 2014)
The mechanical properties of materials printed using fused filament fabrication (FFF) 3D printers typically rely only on adhesion among melt processed thermoplastic polymer strands. This dramatically limits the utility of FFF systems today for a host of manufacturing and consumer products and severely limits the toughness in 3D printed shape memory polymers. To improve the interlayer adhesion in 3D printed parts, we introduce crosslinks among the polymer chains by exposing 3D printed copolymer blends to ionizing radiation to strengthen the parts and reduce anisotropy. A series polymers blended with specific radiation sensitizers, such as trimethylolpropane triacrylate (TMPTA) and triallyisocyanurate (TAIC), were prepared and irradiated by gamma rays. Differential scanning calorimetry (DSC), tensile testing, dynamic mechanical analysis (DMA) and attenuated total reflectance Fourier transform infrared spectroscopy (ATR-FTIR) were employed to characterize the thermomechanical properties and the chemical structure of the various polymers. TAIC was shown to be a very effective radiation sensitizer for 3D printed sensitized polylactic acid (PLA). The results further revealed that crosslinks induced by radiation temperatures near Tg of shape memory systems have prominently enhanced the thermomechanical properties of the 3D printed polymers, as well as the solvent resistance. This enables us to deliver a new generation of inexpensive 3D printable, crosslinked parts with robust thermomechanical properties. [Display omitted] •We prepare acrylate shape memory polymers and poly (lactic) acid derivatives.•We describe mechanical properties of 3D printed, radiation crosslinked polymers.•We show improved resistance to solvents via crosslinking by ionizing radiation.•We demonstrate enhanced toughness via radiation crosslinking.•We study effects of radiation temperature relative to glass transition temp.